Factors influencing training effectiveness among employees at Sharp Manufacturing Corporation (M) Sdn Bhd / Nurul Syahirah Md Yusof - Md Yusof, Nurul Syahirah (Faculty of Business and Management, 2018)
The study is to examine the factor that influencing training effectiveness among the employees at Sharp Manufacturing Corporation (M) Sdn Bhd which is located at Sri Gading, Batu Pahat Johor. To perform this objective, the researcher has extracted three independent variables which are supervisory support, peer support and self-efficacy. A questionnaire with 5 Likert-Scale was used to collect the data among the employees. The samples for this study are the employees at Sharp Manufacturing Corporation (M) Sdn Bhd which is 285 employees as sample size. The sampling technique for this research is proportionate stratified random sampling. The data was analysed using the Statistical Package for the Social Sciences Version 23 (SPSS V.23). This research benefited to the business where the study has been taken which is Sharp Manufacturing Corporation (M) Sdn Bhd. The results will help the company to improve their performance and decision on the company’s training program. They also can encourage employees to attend training program that organised by Human Resource Department of the company. The company will optimize utilisation of all resources for training programs in the future. The finding for this research shows that supervisory support, peer support and self-efficacy have significant relationship towards the dependent variables. In this research also shows that supervisory support is the most influence variable toward training effectiveness.